Stability and beyond-use date of anesthetic agents used in surgical procedures: a review: Stability and Beyond-Use Data of Anesthesia - Wijayanti, Shofia; Hanifah, Suci; Fudholi, Dhomas Hatta (Jurnal Ilmiah Farmasi, 2024)
Background: Anaesthesia drugs are often divided into other syringes to be soluted or mixed with other medications to share with other patients for the sake of efficiency. Objectives: This study aims to know the stability of anesthetic agents and the compatibility with co-simultaneous drugs used. Methods: This review was conducted by searching literature through the following databases: PubMed, Science Direct, and Google Scholar. The keywords used in the search for articles were "stability," "beyond use date," "anesthetic drug," and "intravenous."Results: The data showed that mixing fentanyl with levo-bupivakain or epinefrin is relatively stable up to one month, but it decreases only for 72 hours in dextrose 5% or normal saline (NS). Pethidin can be mixed with acetaminophen and metoclopramide using dextrose, NS, or water and stored up to 24 hours. Midazolam diluted in dextrose 5% (D5) or mixed with other medications maintains stability for up to 14 days or more. Stability of ketamine is 24 hours longer whether it is mixed in solvent or acetaminophen. Mixing with propofol induces instability because of the emulsion form of propofol. Conclusion: In general, the anesthetic drugs of fentanyl, pethidine, midazolam, and ketamine are stable and safe for preparation and administration in more than 24 hours. These four medications are compatible with NS and D5 and all tested medications during 24 hours.